The Abridged Nested Decomposition Method for Multistage Stochastic Linear Programs with Relatively Complete Recourse - Donohue, Christopher; Birge, John (Algorithmic Operations Research, 2006)
This paper considers large-scale multistage stochastic linear programs. Sampling is incorporated into the nested decomposition algorithm in a manner which proves to be significantly more efficient than a previous approach. The main advantage of the method arises from maintaining a restricted set of solutions that substantially reduces computation time in each stage of the procedure.